Mata (Make Activities Be A Safe): Inovasi Platform Digital Berbasis Artificial Intelligence Untuk Meminimalisir Risiko Bagi Penyandang Disabilitas - Ulumi, Helmy Faizi Bahrul; Dzahabiyyati Ulumiah, Dina; Hutabarat, Dony (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The development of the MATA application (Make Activities Be A Safe) is an Artificial Intelligence (AI) based technological innovation to improve the safety and independence of the visually impaired. This service activity uses a research and development method with a design and evaluative approach. The methods used include experiments and Focus Group Discussions (FGDs). Eleven blind students and two accompanying teachers at SKHN 1 Serang City became participants. Results show that the app is effective in detecting obstacles through sound and vibration feedback, as well as increasing user confidence. Constraints include battery power and initial user adaptation. These results demonstrate the importance of policy support for inclusive technology development.